2021
DOI: 10.3390/ma14040905
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Durability Properties of Portland Limestone Cement (PLC) Incorporated with Nano Calcium Carbonate (CaCO3)

Abstract: Despite lower environmental impacts, the use of Portland Limestone Cement (PLC) concrete has been limited due to its reduced later age strength and compromised durability properties. This research evaluates the effects of nano calcium carbonate (CaCO3) on the performance of PLC concrete. The study follows a series of experiments on the fresh, hardened, and durability properties of PLC concrete with different replacement rates of nano CaCO3. Incorporation of 1% nano CaCO3 into PLC concrete provided the optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Thus, the statistical analysis confirmed that nano CaCO 3 outperformed fly ash in most of the tests, with few tests where fly ash showed relatively better results, which, however, were not significant. Further, confirming the previous study by the authors [24], concretes with 1% nano CaCO 3 exhibited a significantly higher performance in all tests (except the ASR) when compared to traditional concretes without nano CaCO 3 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, the statistical analysis confirmed that nano CaCO 3 outperformed fly ash in most of the tests, with few tests where fly ash showed relatively better results, which, however, were not significant. Further, confirming the previous study by the authors [24], concretes with 1% nano CaCO 3 exhibited a significantly higher performance in all tests (except the ASR) when compared to traditional concretes without nano CaCO 3 .…”
Section: Discussionsupporting
confidence: 90%
“…The addition of nano CaCO 3 significantly reduced the expansion of OPC by approximately 45%. The reduced microstructure porosity due to the filling of the micropores of concrete could be one of the major reasons for this reduction in expansion, as explained by Lochana et al [24]. Likewise, the expansion reduced by approximately 20% for PLC concrete.…”
Section: Alkali-silica Reactionmentioning
confidence: 82%
See 3 more Smart Citations